BUILDING A MARKETING STRATEGY FOR CONSUMER BEHAVIOR IN THE INTERNET ENVIRONMENT - KHRUPOVYCH, Svitlana; IVANECHKO, Nelia; NAMISNYAK, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article by the author team is dedicated to studying the changes in consumer behavior strategies on the Internet. The main time frame for analysis is the period of military actions in Ukraine. However, some patterns in the dynamics were also analyzed during the COVID-19 period. A number of factors have been identified as key indicators of consumer behavior on the Internet. It has been established that a large number of buyers trust the quality of well-known brands when choosing products. The authors also argue that the choice of consumers is influenced by friends, relatives, bloggers, and famous media personalities. When forming communication policies, it is important for brand owners to consider the impact of seasonality on consumer choice. It has been established that by analyzing the formation of a customer’s basket on a website, one can determine whether a purchase was impulsive. A list of reasons for forming consumer behavior models on the Internet is proposed. Customer expectations in online stores have been identified, based on the assumption that pricing policies on the Internet will be more favorable than in physical stores. It is hypothesized that the war period has changed the consumer behavior model in the domestic market. Emphasis is placed on the fact that market participants in goods and services have begun to lead a more minimalist lifestyle. Conclusions are also made regarding consumers’ attitudes toward brands, as customers are very sensitive to patriotism and do not allow manufacturers to remain silent about the real situation in Ukraine. Within the framework of scientific research, a quantitative study of changes in consumer behavior was conducted. The results of the study reveal the algorithms for forming marketing strategies for consumer behavior in the online environment. A hypothesis was proposed and confirmed that clients study the value and quantity indicators of products before purchasing them online. The hypothesis was confirmed, based on respondents’ answers, that digital advertising stimulates purchases. It was also found that convenience is the main priority when purchasing online. The research results allowed for the conclusion that the evolution of digital technologies has changed the consumer behavior strategy model in the goods and services market. Ukrainian consumers increasingly prefer online shopping each year, reducing the share of purchases in physical stores. This trend is expected to continue growing.